Efektivitas Layanan Bimbingan Kelompok Teknik Sosiodrama untuk Mengurangi Konformitas Pada Remaja - Darmayanti, Nita; Pohan, Rizky Andana; Chalidaziah, Wan (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2022)
This study aims to determine the effectiveness of sociodrama techniques in reducing conformity to adolescents in Sidodadi Village. This study uses a quantitative approach with a pre-experimental method with a one-group pre-test and post-test design. The research subjects were 10 teenagers who were selected by purposive sampling technique. The instrument used is a conformity scale with 26 items with r = 0.84. data analysis used a paired sample t-test technique with the help of the SPSS 20 application. The themes used in the sociodrama were designed based on themes adapted to the daily lives of teenagers, namely: respecting friends' opinions, not choosing friends, not mocking friends' shortcomings, being obedient what friends ordered and be yourself. The results from the description before being given the sociodrama technique that the average pre-test score was 46.7 which was in the negative category and the results after being given the sociodrama technique the average post-test score was 60.7 which was in the positive category. The results of the analysis of the paired sample t-test, the value of Asymp.sig (2 tailed)/ significant is 0.001 or the probability is below 0.05, the magnitude of t is 4.832.